Producción de un cuento ilustrado mediante técnicas digitales que promueve a los adultos de 40 a 45 años a prepararse en carreras universitarias - Guerrero Gutiérrez, Mélida Paulina (2015)
"Portales inward" is a story illustrated by hand drawing and digital techniques, whose main message is intended to incentivize adult to study a career at the university. The story is based on the biography of a woman who manages to overcome his fears, his age and conformism on social and family comfort, to undertake an adventure that takes her to know herself, giving her bravery to start a new stage of life. This project was carried out based on research, interviews and surveys which led to the development of a colorful, imaginative and with a surreal touch descriptive metaphor. The illustration is an important element of the story, drawn by hand and transferred to digital drawing software, it provides a colorful and visual strength to the contents of this story. The story is intended to produce a personal reflection on the viewer or reader with the message that nothing is impossible in life when it comes to selfimprovement, and that it is important to explore new ways to chart life goals.